Some Techniques Useful in Improving the Precision of Forest Surveys - Rawat, A. S. (Indian Forester, 1961)
In this paper an attempt has been made to describe various methods for obtaining increased precision. Firstly the sampling technique explained and suggested for forest surveys, is stratified random sampling procedure which considerably reduces variability and enhances precision; secondly, the ratio method of estimation has been proposed when the areas of the sampling units are unequal and thirdly, to achieve this end, use may be made of corresponding values collected at some previous date when a hundred percent enumeration was carried out. With a view to illustrate the use of such techniques to working plan practices, solved examples are given and the method of analysis applied in each case explained step by step in Appendices I-III.